(untitled) - Kelly, Gerald (Halow, 2000)
Provides detailed analyses of key topics such as vowels, consonants, stress and intonation, with a variety of sample lessons for each topic. Includes a photocopiable Learner's Reference Chart of English Sounds, a breakdown of common pronunciation errors, and pronunciation and spelling tables
Keywords: English language; Pronunciation